2020
DOI: 10.1210/clinem/dgaa237
|View full text |Cite
|
Sign up to set email alerts
|

Higher TSH Is Not Associated With Thyroid Cancer Risk in the Presence of Thyroid Autoimmunity

Abstract: Background Higher-but-within-normal thyrotropin (thyroid-stimulating hormone, TSH) is associated with higher risk for differentiated thyroid cancer (DTC) in surgical series. Our recent clinical observations suggest that this is not the case in the presence of autoimmune thyroid disease (AITD). We designed the present study to clarify this controversy. Methods We analyzed our prospectively collected database of patients referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[4,7] Thirdly, the improved survival rate and decreased recurrence rate in thyroid cancer patients treated with suppressive doses of levothyroxine supports TSH tropic effect on thyroid tissue promoting neoplasia and carcinogenesis along with oncogenes and other growth factors such as IGF1. [7,8] Albeit many previous studies confirmed an increased risk of malignancy in the thyroid nodules with higher TSH values, even at normal TSH levels, the relationship between TSH levels and PTC is still controversial. [4,8,9] The authors have no funding and conflicts of interest to disclose.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…[4,7] Thirdly, the improved survival rate and decreased recurrence rate in thyroid cancer patients treated with suppressive doses of levothyroxine supports TSH tropic effect on thyroid tissue promoting neoplasia and carcinogenesis along with oncogenes and other growth factors such as IGF1. [7,8] Albeit many previous studies confirmed an increased risk of malignancy in the thyroid nodules with higher TSH values, even at normal TSH levels, the relationship between TSH levels and PTC is still controversial. [4,8,9] The authors have no funding and conflicts of interest to disclose.…”
Section: Introductionmentioning
confidence: 89%
“…[ 5 , 6 ] Secondly, data on other thyroid cancer risk factors and early diagnosis strategies are still insufficient and sometimes expensive and their impact on patient management is still debated. [ 4 , 7 ] Thirdly, the improved survival rate and decreased recurrence rate in thyroid cancer patients treated with suppressive doses of levothyroxine supports TSH tropic effect on thyroid tissue promoting neoplasia and carcinogenesis along with oncogenes and other growth factors such as IGF1. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous study ( 28 , 29 ), we divided AITD patients into two subgroups according to the titer of TPOAb, namely the high-titer TPOAb (H-TPOAb) group (≥100 IU/mL) and the low-titer TPOAb (L-TPOAb ) group (<100 IU/mL). There were 217 H-TPOAb and 129 L-TPOAb subjects in the GD group, while 197 H-TPOAb and 93 L-TPOAb subjects in the HT group respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in children with HT have shown that persistently elevated TSH levels are associated with increased risk of TC [52, 53]. However, a recent study from adult cases showed that in thyroid autoimmunity, TSH concentrations are not associated with the risk of developing differentiated TC [54]. Further studies are needed to address the role of TSH in TC both in the pediatric and adult population.…”
Section: Interrelations Of Stress Autoimmunity Inflammation and Tumor...mentioning
confidence: 99%